Mastering anti-corruption : the practitioners' view - Stachowicz-Stanusch, Agata; Amann, Wolfgang (Contemporary perspectives in corporate social performance and policy (Series), 2019)
"The book Mastering anti-corruption: the practitioners' view is aimed at presenting different ways and modes of mastering anti-corruption in selected countries. By showing examples and cases the authors of particular chapters would like to emphasize the necessity of implementing solutions that will help to prevent corruption at all or at least will diminish its negative effects on business and human beings. The book is divided into four parts: 'Introduction', 'Anti-Corruption as a Topic in Practice - national and international perspective', 'Anti-Corruption as a Topic in Practice - organizational perspective' and 'Anti-Corruption as a Topic in Practice - ethical perspective'. Authors of this book presented a wide range of issues and topics covering the problem of preventing and fighting the corruption around the world. Hopefully the cases will constitute a good practice for countries and nations facing the problem of corruption and will be an inspiration for further research as well as practical applications in this area"--